1988
DOI: 10.1128/jb.170.9.4223-4230.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a Shiga-like toxin type II variant from Escherichia coli strain responsible for edema disease of swine

Abstract: A Shiga-like toxin type II variant (SLT-IIv) is produced by strains of Escherichia coli responsible for edema disease of swine and is antigenically related to Shiga-like toxin type II (SLT-II) of enterohemorrhagic E. coli. However, SLT-IIv is only active against Vero cells, whereas SLT-ll is active against both Vero and HeLa cells.The structural genes for SLT-llv were cloned from E. coli S1191, and the nucleotide sequence was determined and compared with those of other members of the Shiga toxin family. The A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
179
2
3

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(193 citation statements)
references
References 39 publications
9
179
2
3
Order By: Relevance
“…The failure to obtain VT phages from strains of porcine origin confirm the results of Marques et al (1987). Recently, the structural genes for a variant of SLTII, active on Vero but not HeLa cells, have been cloned from total cellular DNA of an E. coli strain causing oedema disease in pigs (Weinstein et al, 1988). These authors concluded that the toxin sequences were chromosomally located.…”
Section: Discussionsupporting
confidence: 59%
“…The failure to obtain VT phages from strains of porcine origin confirm the results of Marques et al (1987). Recently, the structural genes for a variant of SLTII, active on Vero but not HeLa cells, have been cloned from total cellular DNA of an E. coli strain causing oedema disease in pigs (Weinstein et al, 1988). These authors concluded that the toxin sequences were chromosomally located.…”
Section: Discussionsupporting
confidence: 59%
“…VT-1, VT-2, and SLT-II have been shown to bind specifically to globotriaosylceramide (Gb3; Galal-4GalI31-4GlcCer, in which Cer is ceramide) (9,10). Although the B subunit of SLT-II is 84% identical to that of VTE (11,12), the latter was found to bind primarily to globotetraosylceramide (Gb4; GalNAcI31-3Galal-4Ga4j31-4GlcCer) (13, -14) and to a lesser extent to Gb3 (13,14). Because of the homology between the B subunits, we were able to target a limited number of codons in the B cistrons of VTE and VT-1 for site-directed mutagenesis.…”
mentioning
confidence: 99%
“…Why strains carry the genes for two forms of VT is not clear, and how VTl and VT2 each affect the pathogenesis of disease is not fully understood. VTEC associated with pig oedema express a variant of VT2 termed VT2ve (Weinstein et al 1988a). This form of VT is remarkable in that it is lethal for Vero cells but not cytotoxic for HeLa cells.…”
Section: Verocytotoxin-producing E Colimentioning
confidence: 99%